In vivo molecular imaging of gastric cancer by targeting MG7 antigen with confocal laser endomicroscopy - Li, Z.; Zuo, X. L.; Li, C. Q.; Zhou, C. J.; Liu, J.; Goetz, M.; Kiesslich, R.; Wu, K. C.; Fan, D. M.; Li, Y. Q. (Endoscopy, 2013)
Background and study aims: In vivo molecular imaging represents a powerful tool for the immediate diagnosis of gastric cancer. In this study, the monoclonal antibody MG7, which is a specific molecular marker against gastric cancer, was labeled with fluorescent agents to enable in vivo real-time imaging by confocal laser endomicroscopy (CLE). Patients and methods: In vivo molecular imaging was performed in tumor-bearing mice from two kinds of human gastric cancer cell lines. Xenograft tumors were visualized in vivo first with a whole-body fluorescent imaging device and then by CLE using fluorescently labeled MG7 antibody. Gastric cancerous tissue and noncancerous mucosa from human biopsies or surgical specimens were also examined ex vivo by CLE. Results: Intravital imaging of xenograft tumors revealed a specific cellular signal, whereas no specific signal was observed in control tissue or in mice injected with irrelevant antibodies. An ex vivo experiment on human specimens using a rigid confocal probe showed positive fluorescent staining in 22 /23 samples diagnosed as gastric cancer and weak signals in 5 /23 noncancerous tissue samples. CLE evaluation correlated well with immunohistochemical findings. Conclusions: Screening tumors in vivo by CLE may help to detect MG7-Ag-positive tissues, decrease the sampling error by screening the large tumor surface not routinely screened by biopsy or conventional immunohistochemistry, and facilitate early detection of gastric carcinoma.